The Role of Technological Transformation in Supporting Research in Higher Education at the University of Syekh-Yusuf Tangerang - Andi Yustira Lestari Wahab; Andri Kurniawan; Yeni Daniarti; Diah Retno Anggraini; Marrieta Moddies Swara (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
Teaching in higher education is generally carried out by involving a series of methods and technologies for learning and research activities. Many studies have been conducted to examine and evaluate the role of technology and the achievement of learning outcomes in higher education. The article analyzed how the role of technological transformation with all its applications has supported research-based learning activities at Sheikh Yusuf University Tangerang. The method used descriptive qualitative design, and the literature review supports us. Through semi-structured interviews, the researchers obtained many data, then analyzed with a phenomenological approach. The researchers examined the data from interviews. Based on the analysis academic interview data, it can be concluded that the results, including understanding the role of technological transformation with several applications that support research-based learning activities at the higher education level, have been carried out well at Sheikh Yusuf University, Tangerang. Thus, it is hoped that these brief findings can be used as supporting data for similar research in the future. Keywords: Role Technological Transformation, Supporting Research,   Technological Transformation